Pendekatan White Collar Crime: Penanggulangan Tindak Pidana Pembayaran Upah Dibawah Minimum - Datuk Abdul Azizul Hakim; Sumarno Sumarno (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
Abstract: The criminal act of paying wages below the minimum wage is not distinct from the criminal aspect of white collar crime, that is a criminal offense committed by a person with a high socioeconomic status and a respectable commission of a crime in the interest of his work. The corporate criminal acts frequently include white collar crimes. The company's activities give a possibility for white-collar criminality to occur. The study investigates the legal resolution of crimes involving wages below the minimum wage using the white collar crime approach. This is a juridico-normative study employing qualitative data analysis. The juris-normative method is employed to analyze data through a library study on specialized secondary data discussing the norms contained in the provincial minimum wage provisions. Juridic-normative method refers to research that leads to the origins of white-collar crime, specifically in relation to the origins of good faith, with the intention of establishing justice. The results indicate that there are still numerous business owners who do not comply with the regulations. This practice has a significant impact on the well-being of victims of crime earning below the minimum wage. The efficacy of efforts to prevent criminals from receiving below-minimum payments must consider the causes of the crime. The examination of this research found criminological factors in the criminal act of paying wages below the minimum, white collar crime characteristics, and preventive and repressive efforts in the management of white collar crime.